Morphological aspects and expression of estrogen and progesterone receptors in the interdigital sinus in cyclic ewes. Issue 4 (20th February 2014) - Alexandre‐Pires, Graça; Martins, Catarina; Miguel Galvão, António; Correia, Miguel; Ramilo, David; Quaresma, Mário; Ligeiro, Dário; Nunes, Telmo; Manuel Caldeira, Rui; Ferreira‐Dias, Graça
ABSTRACT Many species that belong to Artiodactyls order show an interdigital sinus (IS), as it occurs in sheep, in all four extremities. These are considered to be scent glands responsible for sexual communication having strong attractiveness to mature males at the peak of the breeding season. The aim of this study was to evaluate, in IS in cyclic ewes, the microscopic and ultrastructure (scanning and transmission electron microscopy) anatomy, secretion composition, and mRNA and protein expression of estrogen receptors α and β and progesterone receptors. Glandular sebaceous structures occupy a superficial area of the pouch. The other glands present in the IS show a coiled tubular structure and tall and polyhedral secretory cells with irregular luminal surface resulting from the secretory process. Protein and mRNA gene transcription studies were performed to determine the presence of ER (α and β) and P4r in IS. At the follicular phase, IS cell populations analyzed using flow cytometry expressed higher levels of ERβ compared with ERα (P < 0.05), whereas no difference was observed between them in the luteal phase. The IS amount of secretion was the highest in the follicular phase compared with luteal phase (P < 0.05) or pregnancy (P < 0.001).To the best of our knowledge, for the first time, the presence of ER (α and β) within the IS was demonstrated. As estrogen action is mediated by specific receptors in target cells, the presence of these receptors in IS might be needed to trigger signaling pathways involved in conspecific chemical (sexual) communication attributed to this area. Microsc. Res. Tech. 77:313–325, 2014. © 2014 The Authors Microscopy Research and Technique Published by Wiley Periodicals, Inc.